ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PASIEN DALAM MEMANFAATKAN RAWAT INAP DI RUMAH SAKIT PKU MUHAMMADIYAH NANGGULAN - Muhamad Aminudin; Susanto Susanto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2013)
Hospital as a service provider health is needed to know factors that affect the decision of patient in the harness of hospitalization. Understanding of behavior consumers can be used as an ingredient of consideration for provides maximum service in accordance with consumer advocacy. Knowing the influence of cultural factors, social, personal and psychological to behavior in the harness of inpatient at the PKU Muhammadiyah Nanggulan hospital. This research is research survey analytic with the approach of cross sectional. Population research is patients who harness inpatient PKU Muhammadiyah Nanggulan hospital. The technique sampling in this research is accidental of sampling by the number of sample are 84 people. The data collecting use questionnaire. Analysis of data the use of multiple regressions The result show cultural factors, social factors, personal factors and psychological factors has partial influence to the harness of inpatient care at PKU Muhammadiyah Nanggulan hospital. Cultural factors, social factors, personal factors and psychological factors simultaneously influence to the behavior of patients in the harness of inpatient at the PKU Muhammadiyah Nanggulan Hospital.